1999
DOI: 10.21273/jashs.124.2.189
|View full text |Cite
|
Sign up to set email alerts
|

Water Stress and Crop Level Interactions in Relation to Nectarine Yield, Fruit Size Distribution, and Water Potentials

Abstract: The interactions between irrigation and crop level with respect to fruit size distribution and soil and stem water potentials were investigated in a nectarine (Prunus persica (L.) Batsch. `Fairlane') orchard located in a semiarid zone. Irrigation treatments during stage III of fruit growth ranged from 0.62 to 1.29 of potential evapotranspiration (ETp). Fruit were hand thinned to a wide range of fruit levels (200 to 1200 fruit/tree in the 555-tree/ha orchard). Total yield did … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
34
2
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(48 citation statements)
references
References 25 publications
11
34
2
1
Order By: Relevance
“…1) suggesting that irrigation water requirements in the three treatments plants were attained (Cruz et al, 2012). Also, the similar plant water status found in T0, T1, and T2 plants was in agreement with the results from other authors who showed that the effect of crop load on tree water status is not obvious (Conejero, Ortuño, Mellisho, & Torrecillas, 2010;Naor et al, 1999) or is apparent only under deficit irrigation conditions (Naor, 2004). In contrast, other authors have indicated that crop load may increase transpiration rates (Chalmers, Olsson, & Jones, 1983), stomatal conductance (DeJong, 1986), leaf photosynthesis (Gucci, Grappardelli, Tustin, & Ravaglia, 1995), and tree water use (Mpelasoka, Behboudian, & Green, 2001), probably to compensate for the increased assimilate demand.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…1) suggesting that irrigation water requirements in the three treatments plants were attained (Cruz et al, 2012). Also, the similar plant water status found in T0, T1, and T2 plants was in agreement with the results from other authors who showed that the effect of crop load on tree water status is not obvious (Conejero, Ortuño, Mellisho, & Torrecillas, 2010;Naor et al, 1999) or is apparent only under deficit irrigation conditions (Naor, 2004). In contrast, other authors have indicated that crop load may increase transpiration rates (Chalmers, Olsson, & Jones, 1983), stomatal conductance (DeJong, 1986), leaf photosynthesis (Gucci, Grappardelli, Tustin, & Ravaglia, 1995), and tree water use (Mpelasoka, Behboudian, & Green, 2001), probably to compensate for the increased assimilate demand.…”
Section: Resultssupporting
confidence: 91%
“…In contrast, other authors have indicated that crop load may increase transpiration rates (Chalmers, Olsson, & Jones, 1983), stomatal conductance (DeJong, 1986), leaf photosynthesis (Gucci, Grappardelli, Tustin, & Ravaglia, 1995), and tree water use (Mpelasoka, Behboudian, & Green, 2001), probably to compensate for the increased assimilate demand. In this sense, jujube fruit size did not change with modifications in crop load (Table 1), probably because of the unlimited availability of assimilates as indicated by the similar and very high g lmd values in the three crop load treatments (Naor et al, 1999).…”
Section: Resultsmentioning
confidence: 86%
“…Therefore, changes in fruit FW were probably due to changes in the FW of the flesh and the increased availability of photosynthates from source leaves (DeJong and Grossman, 2005). Similar results have been reported in other studies (Blanco et al, 1995;Berman and DeJong, 1996;Naor et al, 1999;Inglese et al, 2002;Bussi et al, 2005). Moreover, Njoroge and Reighard (2008) found that fruit FW decreased quadratically with increasing time before hand-thinning.…”
Section: Resultssupporting
confidence: 84%
“…Competition for water has been shown to reduce fruit size owing to limitations in cell division and later in cell expansion (Caspari et al 1994;Naor et al 1999) and the competitive effects of grasses, such as maize, with fruit trees are well known (Kumar et al 2001;Tworkoski and Glenn, 2001). It can be surmised that, at the experimental planting densities under Guatemalan climatic conditions, reduced fruit size and mass are likely to be observed when interplanted with maize.…”
Section: Fruit Tree Responsesmentioning
confidence: 99%